Prevalence of an intact hyoid bone at revision excision of a thyroglossal duct remnant. (October 2018) - Huang, Jonathan; Osterbauer, Beth; Koempel, Jeffrey
Abstract: Objective: To determine the prevalence of an intact hyoid bone at the time of revision thyroglossal duct cyst (TGDC) surgery in a pediatric population. Methods: The operative reports of 44 patients under 18 years of age who underwent a revision TGDC surgery from March 1997 to October 2015 at Children's Hospital Los Angeles were reviewed to determine finding of an intact hyoid bone at the time of the revision procedure. Results: At the time of the revision surgery, 75% of the patients had an intact hyoid bone and 25% did not. Conclusion: Patients who experience a recurrence of a TGDC are more likely than not to have an intact hyoid bone at revision surgery. These data indicate that some surgeons are not following the recommendation from Schlange and Sistrunk that removal of the mid-portion of the hyoid bone should be a routine part of any primary procedure for excision of a known or suspected TGDC in order to decrease the risk of recurrence. Despite the prevalent knowledge that the central portion of the hyoid bone be removed during a TGDC procedure, special attention should be given to the area of the midportion of the hyoid bone as a likely site of persistent disease in revision cases even if a previous operative report documents resection of a portion of the hyoid bone and/or cartilage.